Old Aerial View with Matting [Aerial view of San Luis Obispo and Cal Poly to Morro Rock] (1967)
Cal Poly campus can be seen on the right hand side of the photograph, ranging from near the bottom to the middle of the photograph's height. Bishop's Peak is on the middle left of the photograph, and Morro Rock and Pacific Ocean are in the distance, top left. This aerial is looking to the Northwest, and it includes parts of the San Luis Obispo community. This aerial photograph captures eastern San Luis Obispo, Cal Poly including agricultural land, the Los Osos Valley, out to the coast. Morro Bay is visible in the distance, as is the Men's Colony and Camp San Luis. The date is based on similar aerial photographs in the archives that are dated January 18, 1968. The Yosemite residence halls are under construction, as is the pool. Visible is the aero hangar and runway.See a similar photo in greater detail: https://digital.lib.calpoly.edu/rekl-91567